2019
DOI: 10.1242/bio.041343
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of long noncoding RNA GAS5 suppresses tumorigenesis and development of gastric cancer by sponging miR-106a-5p through the Akt/mTOR pathway

Abstract: Long noncoding RNAs (lncRNAs) have emerged as important regulators of human cancers. LncRNA GAS5 (GAS5) is identified as a tumor suppressor involved in several cancers. However, the roles of GAS5 and the mechanisms responsible for its functions in gastric cancer (GC) have not been well documented. Herein, the decreased GAS5 and increased miRNA-106a-5p levels were observed in GC and cell lines. GAS5 level was significantly inversely correlated with miRNA-106a-5p level in GC tissues. Moreover, dual-luciferase re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…In present study, we found that miR-106a-5p was increased in TNBC tissues and cells, and the expression of miR-106a-5p was positively correlated with the tumor grade, which indicated a poor prognosis in TNBC patients. This finding was similar with previous researches targeting on miR-106a-5p and tumor, which also showed an elevation of miR-106a-5p in gastric cancer [ 25 ] and hepatocellular carcinoma [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…In present study, we found that miR-106a-5p was increased in TNBC tissues and cells, and the expression of miR-106a-5p was positively correlated with the tumor grade, which indicated a poor prognosis in TNBC patients. This finding was similar with previous researches targeting on miR-106a-5p and tumor, which also showed an elevation of miR-106a-5p in gastric cancer [ 25 ] and hepatocellular carcinoma [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…An in vitro investigation revealed that GAS5 could suppress pancreatic cancer metastasis 11 . In gastric cancer, overexpression of GAS5 suppresses tumorigenesis and development 12 . However, the potential role of GAS5 in osteosarcoma is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GAS5-targeted miRNA has also been reported in other tumors. For example, GAS5/miR-106a-5p/Akt/mTOR (mammalian target of rapamycin) has been reported in gastric cancer 34 . A bladder cancer study discovered GAS5/miR21/PTEN pathway 32 .…”
Section: Interactions Between Gas5 and Mirnas In Gliomamentioning
confidence: 99%